Hypoxia-induced cardioprotection: A review - Mohammed Abdul, Khaja Shameem; Sen, Alexa; Vikram, Rajeev; Xia, Chenchen; Alshehri, Ahmad A. (Archives of Pharmacy, 2024)
Hypoxia, a state of reduced oxygen availability, exerts complex and often paradoxical effects on the heart. While chronic hypoxia is detrimental and leads to adverse cardiac remodeling and dysfunction, short-term or intermittent hypoxia can contribute towards protective adaptations that enhances the heart’s ability to protect itself from ischemic injury. This protective adaptation, also known as hypoxic preconditioning, drives the activation of several essential signaling pathways, including the hypoxia-inducible factor (HIF) signaling, reactive oxygen species (ROS) signaling, nitric oxide (NO) regulation, and ATP-sensitive potassium channel (KATP) mediated regulation, leading to metabolic reprogramming, angiogenesis with vascular remodeling, and enhanced calcium handling, thereby increasing resistance to ischemic heart disease. We discuss strategies such as hypoxic conditioning and pharmacologically activated HIF signaling, along with targeted approaches to enhance glycolysis and KATP channel regulation and optimize sarcoplasmic reticulum calcium ATPase 2a (SERCA2a) mediated calcium handling in cardiomyocytes. In this review, we explore the mechanisms and therapeutic potential of short-term or intermittent hypoxia-mediated cardioprotection. Additionally, we highlight the importance of addressing challenges and limitations of using hypoxic preconditioning in clinical practice.
Keywords: hypoxia; cardioprotection; hypoxic preconditioning; HIF; ischemic heart disease and heart failure